Biochemical pH clamp: the forgotten resource in membrane bioenergetics. Issue 1 (30th August 2019) - Wegner, Lars H.; Shabala, Sergey
Summary: Solute uptake and release by plant cells are frequently energized by coupling to H + influx supported by the proton motive force (pmf). The pmf results from a stable pH difference between the apoplast and the cytosol, with bulk values ranging from 4.9 to 5.8 and from 7.1 to 7.5, respectively, in combination with a negative electrical membrane potential. The P‐type H + ATPases pumping H + from the cytosol into the apoplast at the expense of ATP hydrolysis are generally viewed as the only pmf source, exclusively linking membrane transport to energy metabolism. However, recent evidence suggests that pump activity may be insufficient to energize transport, particularly under stress conditions. Indeed, cytosolic H + scavenging and apoplastic H + generation by metabolism (denoted as 'active' buffering in contrast to the readily exhausted 'passive' matrix buffering) also stabilize the pH gradient. In the cytosol, H + scavenging is mainly associated with malate decarboxylation catalyzed by malic enzyme, and via the GABA shunt of the tricarboxylic acid (TCA) cycle involving glutamate decarboxylation. In the apoplast, formation of bicarbonate from CO2, the end‐product of respiration, generates H + at pH ≥ 6. Membrane potential is stabilized by K + release and/or by anion uptake via ion channels. Finally, thermodynamic aspects of active buffering are discussed.